Catechists and peasants - Brun, Otto (1984)
Given the enormous field that catechesis covers, I would like to restrict myself in this study to some fundamental aspects of the pastoral experience with catechists. In the South Andean, as in other regions of Peru and the continent, the catechist, part of the poor and believing people, is a fundamental element of the pastoral care of the Church. Knowing the work of the catechist and the history of the catechetical movement in our region, it will be possible for us to see concretely the Church of the Andean South, its insertion in this marginalized and exploited people and from there become aware that the Gospel lived and understood from the "damned of the earth" is indeed a message of liberation and hope.